Pattern sensitive epilepsy: a case report - Kogeorgos, J. (1979)
A child with pattern sensitive epilepsy is reported. She had both absences and generalised seizures. The latter occurred spontaneously but the former followed concentration on patterned materials. These self-induced seizures appeared to have an affective component. The EEG showed generalised atypical spike and wave discharges both in the resting state and during intermittent photic and pattern stimulation. The patient responded to sodium valproate.